Eating Disorders in Males: How Primary Care Providers Can Improve Recognition, Diagnosis, and Treatment - Sangha, Simrin (Am J Mens Health, 2019)
Eating disorders are complex and multifactorial illnesses that affect a broad spectrum of individuals across the life span. Contrary to historic societal beliefs, this disorder is not gender-specific. Lifetime prevalence of eating disorders in males is on the rise and demanding the attention of primary care providers, as well as the general population, in order to negate the potentially life-threatening complications. Current literature has continued to reinforce the notion that eating disorders predominately affect females by excluding males from research, thereby adding to the void in men-centered knowledge and targeted clinical care. To determine what is currently known about eating disorders among males, a scoping review was undertaken, which identified 15 empirical studies that focused on this topic. Using the Garrard matrix to extract and synthesize the findings across these studies, this scoping review provides an overview of the contributing and constituting factors of eating disorders in males by exploring the associated stigmas, risk factors, experiences of men diagnosed with an eating disorder, and differing clinical presentations. The synthesized evidence is utilized to discuss clinical recommendations for primary care providers, inclusive of male-specific treatment plans, as a means to improving care for this poorly understood and emerging men’s health issue.